Multidimensional Transcriptomics Reveals the Key Genes and Pathways Regulating the Acidity of Apples - Wenyuan Yang; Hang Yu; Lian Tao; Hongjiang Xie (Current Issues in Molecular Biology)
Low-acid apples are popular among consumers, but the mechanisms behind the complex differences in acidity among varieties that are caused by high altitude are not clear. In this study, we used the ‘Golden Delicious’ apple and its superior variant in the Western Sichuan Plateau of China to analyze organic acid composition, content, and the expression levels of related regulated genes during fruit development. We found that the organic acid content in the variant was significantly lower than that in the ‘Golden Delicious’ apple. In both apples, quinic and malic acids were the predominant organic acids, while citric and tartaric acids were present in lower amounts. In this multidimensional regulatory study, we used transcriptome sequencing, cluster analysis, and weighted gene co-expression network analysis (WGCNA) to reveal that differentially expressed genes are enriched in multiple pathways affecting fruit acidity during apple development; malate dehydrogenase (MDH) affects the malic acid content of fruits of different varieties; and H+-ATPase (VHA) mainly regulates the content of vacuolar organic acids, which affects fruit acidity. Additionally, we performed qRT-PCR experiments to validate our results. This study provides molecular insights into the mechanisms by which low-acidity traits form in apples and offers a theoretical basis for regulating the flavor of fleshy fruits.